Organizational commitment of Ilonggo millenials across different industries - Alimo-ot, Armarie; Encarnacion, Jinno; Hiballes, Ryan Vincent; Montes, Karima Krista
Human capital is the greatest asset that determines the performance of a firm in reaching its objectives and be competitive. The millennial generation born from the 1980s to early 2000s begin to enter and influence organizational workplaces. They have become the fastest growing segment of the workforce and thrive in a fast-paced, technologically advanced, and globalized world. However, millennials in the workplace express little commitment to employers and stay only for a short-term. Firms are being challenged as millennials believe they are beingunderutilized, not being developed as future leaders of organization despite expressing a positive view for business' role in society. Consequently, organizations must prepare for this generations in order to provide the most appealing and attractive environment.This study focused on normative, affective, and continuance factors to determine the organizational commitment of millennial in the top five (5) employing industries of Iloilo City namely BPO, Baking and Finance, Food and Restaurants, Real Estate and Health Service. Factors wereranked based on what millennials perceive as the most important factor that affects organizational commitment. The study also focused on determining whether there is a significant difference between demographic characteristics which are personal job, andorganizational; and the study compared the differences in organizational commitment in contrast to the result across the various industries. To gather the needed data, the researchers conducted an online survey to one hundred (100) respondents represented by twenty (20)respondents from each of the five (5) industries. Results were generated and analyzed through a Statistical Package social /science (SPSS) software. Frequency distribution was conducted in order to attain the mean averages between factors that resulted to the level of organizationalcommitment of Ilonggo millennials. Normative commitment measured at 4.37, affective commitment at 4.64, and continuance commitment measured at 4.40 level. Cross tabulation was used to determined and rank the interest, jobs that are appealing what millennials want,and the type of jobs they want to have across five (5) industries. The results were determined as competitive salaries being the most important factor that will affect organizational commitment, with company benefits such as health insurance as the second most important,and work-life balance in third rank. While, One-way Anova was used to determine whether there is a significant difference between personal, job and organizational characteristics of millennials across different industries. The result showed that there are two significantdifferences among factors. These are job level and salary which are significant at p>0.05 level, 0.0246 and 0.032, respectively. It also resulted in the Real Estate Industry being the only industry with a significant difference as their level of commitment is higher with the jobs skills (managerial position, supervisor, team leader) and high competitive salary.